Formulas2

Formulas2 - d d n f ( x + h) - f ( x ) nx n-1 u = f ( x ) ,...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: d d n f ( x + h) - f ( x ) nx n-1 u = f ( x ) , v = g ( x ) x = [ uv ] = u ' v + uv ' hf 0 dx h dx d x d u ' v - uv ' u dy dy du d n nu n-1 u ' = u = ex = . e = 2 dx v v dx dx du dx dx f ' ( x ) = lim d u' [ ln u ] = dx u g ' ( y0 ) = E= d u eu u ' e = dx d x a x ln a a = dx d u a u a ' a = ln u dx d 1 [ ln x ] = dx x f ( x ) - f ( a ) = f '( a ) ( x - a ) f has point f ( x ) f f ( a ) + f '( a ) ( x - a ) and g has the point 1 g ( x ) = f -1 ( x ) f ' ( x0 ) n x dx = ( x0 , y0 ) ( y0 , x0 ) x f '( x) f ( x) 1 n+1 x +C n +1 kf ( x) dx = k f ( x) dx 1 dx = ln| x | + C x a x dx = 1 x a +C ln a [ f ( x) g ( x)]dx = f ( x) dx g ( x) dx x x e dx = e + C 1 ax ax e dx = e + C a b lim n lim n lim n * f ( x k ) x = f ( x k -1 )x = f ( x k )x = f ( x) dx n k =1 n k =1 n k =1 a b a f ( x) dx = b F ( x ) = F ( b) - F ( a ) a b b a a f ( x) dx = - f ( x) dx a b b a a a f ( x) dx = 0 af f ( x) dx = a ( x) dx a b f f f ( x) dx = ( x) dx + ( x) dx a c b b b c b dx f g af ( x) + bg ( x ) = a ( x) dx + b ( x) dx a a a a b d b( t ) f ( x) dx = - F ' ( t ) = - f ( t ) f ( x ) dx = f ( b ( t ) ) b ' ( t ) - f ( a ( t ) ) a ' ( t ) t dt a( t ) 1 n+1 1 u u n dx = ln| u | + C e du = e + C u du = u +C u n +1 u dv = uv - v du f ( x) dx = F ' ( t ) = f ( t ) d dt d dt t FA07 T2A 2007 Arizona State University, Department of Mathematics and Statistics 1 ...
View Full Document

Ask a homework question - tutors are online